Use of modern techniques and ways to activate them to improve the performance of general education schools in the State of Palestine in the light of recent trends - Shaheen, Fadi Ahmad (Journal of Educational and Psychological Sciences, 2024)
The present study aims to identify the use of modern techniques and the ways in which they can be used to improve the performance of general education schools in the State of Palestine in the light of recent trends. The study relied on the analytical and documentary descriptive methodology for gathering information from its various sources and then subjected to scrutiny and scrutiny. The research was divided into an introduction, four investigations and a conclusion. As described below and included above, the problem of research, its questions, its objectives, its importance and its methodology. The first was to discuss the concepts of learning and education, the difference between them and the interrelationship between them. The second discussed the importance of methods and techniques, and in the third, the types of methods and techniques used in the teaching process. The fourth research focused on what should be taken into account when using these techniques. The conclusion of the researcher ' s summary of the main findings, recommendations and proposals, through this examination, could guide some of the recommendations and could be summarized as follows:1. The need to choose tools and techniques with great care is not the goal of gathering as much means as possible, but must be relevant to the subject matter of the study and the creation of the motivation of the student and teacher.